Incompressible polar active fluids in the moving phase in dimensions d > 2. (23rd November 2018) - Chen, Leiming; Lee, Chiu Fan; Toner, John
Abstract: We study universal behavior in the moving (polar ordered) phase of a generic system of motile particles with alignment interactions in the incompressible limit for spatial dimensions d  > 2. Using a dynamical renormalization group analysis, we obtain the exact dynamic, roughness, and anisotropy exponents that describe the scaling behavior of such incompressible systems. This is the first time a compelling argument has been given for the exact values of the anomalous scaling exponents of a flock moving through an isotropic medium in d  > 2.